2018
DOI: 10.1155/2018/7297945
|View full text |Cite
|
Sign up to set email alerts
|

Back Analysis and Calculation of Dynamic Mechanical Parameters of Rock Mass with Measured Blasting Vibration Signals

Abstract: How to obtain dynamic parameters of rock masses quickly and precisely is a popular and difficult problem, which plays a very important part in engineering design or construction. Currently, the methods used to obtain these parameters are in situ testing method, empirical formula, and so on. However, these methods have some shortcomings, such as large investment and long construction period, which cannot obtain the dynamic parameters precisely and quickly in the engineering scale. In this study, a new method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…e two important steps of quantification and regional segmentation were studied, and a blasting rock distribution model with strong applicability and high processing efficiency was established, and a software package for automatic determination of ore block degree was developed [13][14][15]. However, the above research has not solved the corresponding problems well, so this paper puts forward the following innovations: ① Combining genetic algorithm and BP algorithm, a computer image recognition algorithm based on GA-BP depth neural network is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…e two important steps of quantification and regional segmentation were studied, and a blasting rock distribution model with strong applicability and high processing efficiency was established, and a software package for automatic determination of ore block degree was developed [13][14][15]. However, the above research has not solved the corresponding problems well, so this paper puts forward the following innovations: ① Combining genetic algorithm and BP algorithm, a computer image recognition algorithm based on GA-BP depth neural network is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Results from Haghnejad et al [20] also showed that the blasting damage factors D and GSI play important roles in slope damage. Yang et al [21] used the rock acoustic P-wave velocity as a supplemental element to estimate the disturbance factor D and compensate for the disturbance factor D in the H-B failure criterion. Yang et al [22] investigated the relationship between the disturbance factor D and the damage depth based on rock acoustic wave velocity test results after blasting and studied the detrimental effects on the mechanical properties of the rock.…”
Section: Introductionmentioning
confidence: 99%
“…Blasting is generally the initial stage of rock breakage in mines, quarries, or geotechnical constructions, and its outcome plays a strong role in all downstream operations, such as loading, hauling, and crushing [1][2][3][4]. In practice, bench blasting is the most widely used operation pattern [5,6]. However, oversize boulders and rock toes that significantly affect the efficiency and cost of downstream operations often appear in the conventional bench blasting [7].…”
Section: Introductionmentioning
confidence: 99%